We start with the following equality:0 = 0
We can write equality as follows:3-3 = 4-4
We highlight 3 and 4:3 (1-1) = 4 (1-1)
We cut the common terms in parentheses and come to equality:3 = 4
Obviously this demonstration has an error because we all know that 3 is not equal to 4 (or does anyone have any questions?). Click below to find out what the error is:
In this demonstration comes a stage where we have:
3 (1-1) = 4 (1-1)
According to the demonstration, the next step is to cut the common members in parentheses.
There is the mistake !!!
It's wrong because what we have in parentheses is 1-1, which is 0. So we would be dividing both sides by zero. Division by zero does not exist !!!Next: 7 is equal to 8?